2012
DOI: 10.4238/2012.april.19.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with body weight and abdominal fat traits on chicken chromosomes 3, 5 and 7

Abstract: ABSTRACT. Body weight and abdominal fat traits in meat-type chickens are complex and economically important factors. Our objective was to identify quantitative trait loci (QTL) responsible for body weight and abdominal fat traits in broiler chickens. The Northeast Agricultural University Resource Population (NEAURP) is a cross between broiler sires and Baier layer dams. We measured body weight and abdominal fat traits in the F 2 population. A total of 362 F 2 individuals derived from four F 1 families and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 35 publications
(47 reference statements)
0
30
0
1
Order By: Relevance
“…By 2001, however, chicken producers could rear chickens to their final body weight of 2.5 kg in a fattening period of only 42 days (Havenstein et al, 2003; Flock et al, 2005). Chickens have been genetically improved for increased body weight gain, feed efficiency, growth rate, and breast muscle weight to meet the requirements of consumers (Wang et al, 2012). These selection processes have produced modern commercial chicken lines with a higher growth rate, breast meat yield and better feed conversion rates, and a higher body fat compared with unselected lines (Baéza and Le Bihan-Duval, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By 2001, however, chicken producers could rear chickens to their final body weight of 2.5 kg in a fattening period of only 42 days (Havenstein et al, 2003; Flock et al, 2005). Chickens have been genetically improved for increased body weight gain, feed efficiency, growth rate, and breast muscle weight to meet the requirements of consumers (Wang et al, 2012). These selection processes have produced modern commercial chicken lines with a higher growth rate, breast meat yield and better feed conversion rates, and a higher body fat compared with unselected lines (Baéza and Le Bihan-Duval, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Szapacs et al [34] showed that when APOA1 was exposed to oxidative changes, the formation of HDL and its exportation to the liver were altered. In chicken, GGA7, which is homoeologous to APL7, carries numerous QTL related to abdominal fat [35, 36]. Taken together, these results strengthen the hypothesis that chromosome APL7 is important in “fat” metabolism and further studies will be required to identify the genes that underlie the QTL and pQTL mapped to this chromosome.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, studies on the chicken genome have been of great value to both agriculture and medicine (Wang et al, 2012a). Therefore, studies on the chicken genome have been of great value to both agriculture and medicine (Wang et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%